Clinical symptoms and blood concentration of new psychoactive substances (NPS) in intoxicated and hospitalized patients in the Budapest region of Hungary (2018-19). (2nd January 2022) - Institóris, László; Kovács, Katalin; Sija, Éva; Berkecz, Róbert; Körmöczi, Tímea; Németh, István; Elek, István; Bakos, Ágnes; Urbán, Ildikó; Pap, Csaba; Kereszty, Éva
Abstract: Background: New Psychoactive Substances (NPS) impose a new challenge on the legal and health care system, yet, there is little information available about how new substances spread based on hospitalization of intoxicated patients. The aims of this study were: (i) to investigate the frequency of NPS among suspected drug intoxicated patients, (ii) to study the connection between blood concentration and clinical symptoms, (iii) to determine their half-life with a time-series blood sampling protocol. Methods: During the observation period, 116 suspected drug intoxicated patients were sampled. The samples were analyzed for alcohol, 20 classical illicit and licit drugs, and for 78 NPS. Clinical symptoms were registered on-site (by the Emergency Medical Services) and (also) at hospital admittance. Results: NPS were detected in 51 patients of which cathinones were found in 4, the synthetic cannabinoids (SCs) 5 F-MDMB-PINACA and 5 F-MDMB-PICA in 23-23, and CUMYL-CH-MEGACLONE in 2 cases. Poison severity scores (PSS) showed mild to moderate intoxications overall. Connection between blood concentration and severity of clinical symptoms were inconclusive. The calculated half-life of 5 F-MDMB-PINACA and 5 F-MDMB-PICA was 2.50 and 2.68 h, respectively. Conclusion: The ratio of SCs among the selected intoxicated patients was higher than expected from seizure data which could be the consequence of targeted patient selection. The clinical symptoms and the severity of intoxication cannot be characterized simply by NPS blood levels. The short half-life of SCs can explain the relatively rapid consolidation of intoxication symptoms. Highlights: In the Budapest region, the majority of hospitalized NPS intoxications was caused by the synthetic cannabinoids 5F-MDMB-PINACA and 5F-MDMB-PICA in 2018-19. No correlation between blood concentration and symptoms severity could be established. The clinical symptoms of synthetic cannabinoid users improved quickly and no ICU treatment was necessary. The half-life of 5F-MDMB-PINACA and 5F-MDMB-PICA was proved to be 2.50 hours and 2.68 hours, respectively.